Rapid profiling of triacylglycerols for identifying authenticity of edible oils using supercritical fluid chromatography-quadruple time-of-flight mass spectrometry combined with chemometric tools. Issue 21 (17th May 2016) - Tu, Anqi; Du, Zhenxia; Qu, Shuping
Abstract : A rapid method was developed for identifying the authenticity of edible oils using SFC-Q-TOF-MS combined with PCA. Abstract : Triacylglycerol (TAG) as the major ingredient of oil is a key indicator for the identification of oil adulteration due to its characteristic distributions in different oils. In this research, a high-throughput method for rapidly detecting acylglycerols in various edible oils was established by applying supercritical fluid chromatography (SFC) coupled with quadruple time-of-flight mass spectrometry (Q-TOF-MS), without any sample pretreatment procedure. The retention mechanism of TAGs on different columns were comprehensively evaluated including the previous work on an ODS column, as well as our study on HSS C18 SB, BEH and BEH 2-EP columns. Distinctive retention of our method allows the separation of certain pairs of TAGs which remains difficult by traditional methods, and the analysis time is greatly reduced. SFC-MS data were subsequently analysed by principal component analysis (PCA) to make a clear classification between six different kinds of vegetable oils, showing its potential in differentiating the fakes quickly. Considering the high-price of olive oil, further quantification of olive oil adulteration was studied by estimating known and unknown compositions of blend oils according to the curves of areas of selected TAG markers versus adulterant concentrations. Good consistencies with the labeled content of olive oil in commercial blend oils demonstrated the reliability of the quantitative method, and these blend oils were differentiated distinctly from pure olive oils in the score plot of a PCA model. To the best of our knowledge, it was the first time that the retention of TAGs using different stationary phases in a SFC system was discussed, and that SFC was applied to quantify oil adulteration. This fast and effective method is of great advantage to authenticate edible oils.